The Impact of Quality Management on Employee Retention and Turnover Intention in Small and Medium-Sized Enterprises - Aghdasi, Mohammad; Rejali, Hora (Future of Work and Digital Management Journal, 2026)
In today's fast-paced and highly competitive environment, small and medium-sized enterprises (SMEs) play a crucial role in the economic development of countries. However, one of the major challenges facing these organizations is employee retention and the prevention of workforce turnover. Employee turnover is a complex and multifaceted phenomenon that can lead to reduced productivity, increased recruitment and training costs, and the erosion of an organization's competitive advantage. In this context, quality management, as one of the fundamental components of organizational performance improvement, can play a significant role in enhancing job satisfaction, increasing organizational commitment, and ultimately reducing turnover rates. The primary objective of this study is to evaluate the role of quality management in human resource retention, with a particular focus on the factors influencing employees' turnover intentions in small and medium-sized enterprises. In other words, this study seeks to answer the key question of whether the implementation of quality management principles and practices can influence employees' decisions to remain with the organization. The research employed a descriptive-survey design. Data were collected using two standardized questionnaires: a Quality Management Questionnaire and a Turnover Intention Questionnaire, which measures employees' propensity to leave the organization. The study population for the turnover intention questionnaire consisted of employees working in active SMEs in Iran, while the study population for the quality management questionnaire consisted of managers of these organizations. To analyze the data, appropriate statistical models, including multiple regression analysis using the Enter method, were applied to examine the relationships among variables accurately. The statistical analyses indicate that all dimensions of the quality management system, including organizational structure, leadership, planning, support, operational activities, employee identification and training, empowerment, performance evaluation, and continuous improvement, are significantly associated with reduced employee turnover intention. These findings demonstrate that the implementation of comprehensive quality management processes not only enhances organizational performance but also serves as an effective strategy for controlling and reducing employee turnover rates. Overall, the results of this study emphasize the importance of quality management and demonstrate that improving quality across different organizational levels not only leads to enhanced operational performance but also serves as a critical factor in preserving organizational human capital and preventing employee turnover.